Impact Of Differential Pair Routing Discontinuities On Signal Integrity In Printed Circuit Board Design - Adanan, Omar Mukhtar (2013)
Differential pair routing on Printed Circuit Board (PCB) is widely used as interconnect due to its excellent signal integrity performance, However, differential pair is not immune to the impact of routing discontinuities. This research analyzed and quantified the impact several types of routing discontinuities on differential pair. These routing discontinuities are routing over split plane, routing over void, 45° bend routing and serpentine routing. The results of this research are based on Full-wave 3D modeling and simulation. The cross-sectional differential pair configuration parameters are based on SATA 3rd Generation industrial standard. Four types of analysis have been done for each of the routing discontinuities, which are S-parameter, TDR, Model Eye-Diagram and Full Channel Transient Analysis. Based on configuration parameters used in this research, the differential pair routing with routing discontinuities degrade the signal integrity performance especially above 3GHz. Routing discontinuities also cause the characteristic impedance of differential routing to change and lead to impedance mismatch. Different types of routing discontinuities have different impact characteristics. As for routing over split plane and void, the higher the number of split planes or voids higher the degradation in signal integrity. As for serpentine and 45° degree bend, inconsistence spacing within differential pair traces causes the signal integrity performance to degrade. x